Implementación de Buenas Prácticas de Manufactura en la empresa Lácteos La Esencia del cantón Santiago de Píllaro, Provincia de Tungurahua. - Villacrés Haro, Yoselin Selena (2022)
The actual research work was performed into Esencia dairy enterprise from Santiago de Píllaro canton, Tungurahua province, with the purpose to perform the Good Manufacturing Practices Implementation (GMP) regulations, for this, it was made requirements study diagnosis, by the initial check list application; it reported about a 54.5% overall compliance. To achieve each one the aims this work, it was made surveys on workers and owners, by addressing general BPM issues within: documentation, infrastructure, training, management staff, equipment and utensils, storage and finished product distribution, as a basic requirement within of the food innocuousness, for this, it was built action plan based on the non-conformities found into analysis. It was made audits, through a check list by knowing the critical points, what require BPM implementation. Once, it has been achieved the proposed aims, it is identified, what the highest non-compliance percentage, regarding BPM is found into good practices installations and requirements, production operations, quality assurance and control, among others, which directly, affect to the finished product innocuousness, what it was proposed to make the manual implementation, by performing changes into infrastructure, the areas, so that they have an easily cleaned, it was put signage for a better identification, it was trained the staff in the correct hands washing, cleaning and disinfection processes, it was improved the raw material analysis, the same way was improved the electrical installations and the adequate equipment for the enterprise's staff. Once, it was finished the BPM implementation process, the enterprise, now meets 96.4% percent of requirement. It is essential the BPM Manual elaboration and implementation set in the Executive Decree 3253 from Ecuador that ensures the products quality.